(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article reflects its author’s view of the functional opportunities of today’s Russian ERP (Enterprise Resource Planning) systems in the remit of the continuing transition of Russian enterprises to the software produced mainly Russian developers. The peculiarities of the present stage in the evolution of Russian integrated data analytics systems targeted at business management and decision support, are shown with consideration to the primary objectives faced by the Russian IT industry with respect to the achievement of a technology level amounting to the foreign software managing finance and performing other functions in planned economy. Analyzed are the latest tendencies in architecture and in the promotion of Russian ERP systems in the domestic market; revealed are those factors that hamper more active use of the same.